2014
DOI: 10.1371/journal.pone.0103957
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of the Mid1/Cch1/Yvc1 Calcium Channels in Aspergillus fumigatus Virulence

Abstract: Aspergillus fumigatus is a major opportunistic pathogen and allergen of mammals. Calcium homeostasis and signaling is essential for numerous biological processes and also influences A. fumigatus pathogenicity. The presented study characterized the function of the A. fumigatus homologues of three Saccharomyces cerevisiae calcium channels, voltage-gated Cch1, stretch-activated Mid1 and vacuolar Yvc1. The A. fumigatus calcium channels cchA, midA and yvcA were regulated at transcriptional level by increased calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 74 publications
1
41
0
Order By: Relevance
“…[46][47][48] For example, similar to the DcnaA (catalytic subunit of the calcineurin) mutant, we found that FlcA was required for A. fumigatus colony extension and influenced hyphal branching. The DflcA mutant was more sensitive to calcium and cyclosporine, excess of metals, and cell wall and oxidative stressing agents.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…[46][47][48] For example, similar to the DcnaA (catalytic subunit of the calcineurin) mutant, we found that FlcA was required for A. fumigatus colony extension and influenced hyphal branching. The DflcA mutant was more sensitive to calcium and cyclosporine, excess of metals, and cell wall and oxidative stressing agents.…”
Section: Discussionmentioning
confidence: 65%
“…56 The DNA fragments together with plasmid linearized pRS426 BamHI/ EcoRI were transformed into S. cerevisiae strain SC9721 (FGSC) by the lithium acetate method 57 and DNA of the transformants extracted as previously described 58 TaKaRa Ex Taq TM DNA Polymerase (Clontech Takara Bio) was used for DNA amplification and Southern blot analyses demonstrated that the transformation cassettes had integrated homologously at the targeted A. fumigatus loci. A. fumigatus transformation was performed as described by de Castro et al 48 The complementing strains were constructed by first isolating from the corresponding deletion strain, a pyrG ¡ auxotroph sector resistant to 0.75 mg/ml of 5-FOA (5-Fluoroorotic acid, Sigma-Aldrich), a fluorinated derivative of the pyrimidine precursor orotic acid. This analog was used to select for the absence of a functional pyrG C gene, which encodes the enzyme for the decarboxylation of 5-fluoroorotic acid to 5-fluorouracil, a toxic metabolite.…”
Section: Construction Of the A Fumigatus Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HACS consists of two putative proteins, Cch1p and Mid1p, which are expressed and colocalize to the plasma membrane in a variety of fungi, such as the saprophytes Schizosaccharomyces pombe and Neurospora crassa (41,42), the animal-pathogenic fungi Candida albicans and Cryptococcus neoformans (43)(44)(45), and the plantpathogenic fungi Gibberella zeae, Claviceps purpurea, and Uromyces appendiculatus (46)(47)(48)(49). Notably, Aspergillus species (50,51) express the putative Ca 2ϩ channel homologs of CCH1 and MID1, namely, cchA and midA, whose topology is similar to the overall topology of Ca 2ϩ voltage-gated channels in higher eukaryotes. These channels play unique and complex roles in low-calcium environments.…”
Section: Calcium Influx System On Cell Membranementioning
confidence: 99%
“…CCH1 also plays a role in mediating the virulence of C. neoformans and is required for the growth of C. neoformans at low extracellular Ca 2ϩ concentrations, especially at mammalian body temperatures (45). In aspergilli, the homologs of CCH1 and MID1, cchA and midA, not only have the functional benefits of fast growth but also play important roles in calcium homeostasis and virulence (50,51).…”
Section: The Roles Of Calcium Signaling In Fungal Cell Survivalmentioning
confidence: 99%